Analysis of the Student’s Creative Thinking Skill in Science Learning in Primary Schools of Rappocini Makassar City - Yanti, Andi Astri; Wiyanto, Wiyanto; Lisdiana, Lisdiana (Postgraduate, Universitas Negeri Semarang, Indonesia, 2018)
The ability of students in solving problems in science learning is influenced by the thinking skills that determine how people solve problems, make decisions, and understand something. This study aimed to describe the creative thinking skills of students in science learning. The study was conducted in SDN Gunung Sari 1, SDN Gunung Sari 2, SD Inpres BTN IKIP I , and SD Inpres BTN IKIP II Makassar BTN 2017/2018 school year. The study was conducted on 12 students from four schools. The data collection technique using observation, testing and interview. The study was conducted in three stages, starting with the observation during the learning takes place, then give the creative thinking skills test item and continue to do the interview. The results showed that most of the students have a high creative thinking skills. It can be concluded students with the attitude of creative thinking skills high skill fluency, flexibility, Originality, and elaboration and students with the process of creative thinking skills high skill imaginative, feel challenged, dare to take risks, and appreciate nature.